IMPULSE BUYING, PERSONALITY TRAITS, IN-STORE ATMOSPHERICS, AND THEIR INTERACTION - jalan, nikhil (2006)
In today's Post-modern Era shopping is has become a social and leisure activity, reducing the number of cognitively planned purchases made by consumers. Hedonic and pleasure driven shopping endeavors have led to the rapid increase in impulse buying, making it common place and socially acceptable. Even though, most impulse decisions are made when consumers are inside the store, the effect of in-store stimuli on such decisions has not been adequately explored. This has led to the purpose of this research, which is to understand the interaction between consumers' affective states and in-store stimuli, with respect to impulse buying. In keeping with the exploratory nature of the research, an interpretivist approach was employed to collect data on the garment shopping behaviour of young females, through semi-structured, in-depth interviews. The analysis of the information gathered highlights the importance of in-store stimuli on impulse buying as well as illustrates its interaction with consumer specific variables and affective states. Since, multiple interactions and associations are possible, the study implies that retailers should seek to design the in-store environment in such a manner in which it can have the greatest impact on its primary target segment.